2009
DOI: 10.1164/rccm.200802-232oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Systemic Inflammation on Inspiratory and Limb Muscle Strength and Bulk in Cystic Fibrosis

Abstract: In patients with CF, the intensity of systemic inflammation does not account significantly for the variance of FFM and diaphragm or limb muscle strength and bulk. Training of the diaphragm in CF occurs despite the presence of systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 35 publications
8
34
0
Order By: Relevance
“…This finding complies with studies that demonstrated that in some situations the cytokines may get compartmentalized, for example, in the lungs, or because most of patients were clinically stable (CRP <0.5 mg), or by the inclusion of the study on those using ibuprofen and azithromycin [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…This finding complies with studies that demonstrated that in some situations the cytokines may get compartmentalized, for example, in the lungs, or because most of patients were clinically stable (CRP <0.5 mg), or by the inclusion of the study on those using ibuprofen and azithromycin [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…In these patients inflammation was not identified as a predictor of respiratory muscle compromise, whereas fat-free mass and airway resistance were. 38 In our cohort of CF subjects with mild lung disease, diaphragm thickening might have not yet occurred, and the respiratory muscles might have been exposed to the deleterious effects of chronic infection and malnutrition in the absence of a counterbalancing diaphragm thickening mechanism.…”
Section: Discussionmentioning
confidence: 81%
“…15 It has been suggested that decreased muscular synthesis and impaired muscle regeneration occur in the presence of abundant pro-inflammatory cytokines in the chronically infected lung, which spill over and cause chronic systemic inflammation. 38 Recent work addressed sex differences in the course of P. aeruginosa infection in patients with CF, and highlighted that estrogen induces mucoid conversion of P. aeruginosa in women with CF and is associated with more frequent exacerbations. 6 On the other hand, male CF patients with impaired skeletal muscle strength have normal testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published human studies of IL-17 in CF are rare but some support the importance of this axis. Increased levels of IL-17 have been found in bronchoalveolar lavage (BAL) of children and adults during infective exacerbations and in the serum of clinically stable adults [16][17][18][19]. In addition, people with CF who exhibit robust T-cell responses to Pseudomonas aeruginosa manifest more severe lung disease [20].…”
mentioning
confidence: 99%